2019
DOI: 10.3390/insects10120428
|View full text |Cite
|
Sign up to set email alerts
|

A Glycoproteinaceous Secretion in the Seminal Vesicles of the Termite Coptotermes gestroi (Isoptera: Rhinotermitidae)

Abstract: Coptotermes gestroi is a subterranean termite with colonies generally headed by a pair of primary reproductives, although neotenics may occur. In this study, the male reproductive system was compared during different life stages of nymphs, alates, neotenic reproductives, and kings of C. gestroi, focusing on the modifications of this system along the maturation of these individuals. The structure of the male reproductive system follows the pattern described for insects, although C. gestroi males do not exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Previous analyses on the seminal vesicles of different termite species, including C. gestroi , revealed that these structures secrete a content that reacts positively to xP and PAS tests (Laranjo et al, 2019, 2020). Then, similar to the spermathecae, the seminal fluid transferred to the female apparatus during copulation is likely to contain proteins and polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analyses on the seminal vesicles of different termite species, including C. gestroi , revealed that these structures secrete a content that reacts positively to xP and PAS tests (Laranjo et al, 2019, 2020). Then, similar to the spermathecae, the seminal fluid transferred to the female apparatus during copulation is likely to contain proteins and polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive studies regarding this species are quite difficult due to its cryptic habit and the occurrence of satellite nests (Lelis, 1999). Thus, rearing laboratory colonies is a suitable way to conduct comparative analyses on different‐aged reproductives (Laranjo et al, 2019). Aiming to contribute to the knowledge about termite reproduction and sperm storage dynamics, we provide a comparative analysis on the morphometry and morphophysiology of the spermathecae of virgin and inseminated queens of C. gestroi .…”
Section: Introductionmentioning
confidence: 99%
“…The final products of spermiogenesis in A. amphitrite are the spermatozoa, which migrate from the seminiferous tubules to the vas deferens and are mixed with an amorphous matrix secreted from the vesicles. It is suggested that the physiological importance of the secretion could lie in its ability to nourish spermatozoa and maintain their fertility (Laranjo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In Southeast Brazil, buildings infested by C. gestroi were first reported in 1923; since then, this species has been an important structural and economic pest (Martins et al ., 2010). However, its reproductive biology has been poorly investigated (Laranjo et al ., 2019), especially regarding nymph, alate, and neotenic differentiation, and ovarian development during the lifecycle of the females. Termite females possess ovaries constituted of panoistic ovarioles, which are found in primitive insect groups, and are characterized by the absence of specialized nurse cells (Büning, 1994).…”
Section: Introductionmentioning
confidence: 99%